Self-Expandable Metallic Stent Placement for Radiation-Induced Esophageal Stricture: A Case Report - Annisa Zahra Mufida; Amie Vidyani; Andi Ratna Kartika Maharani; Amal Arifi Hidayat; Titong Sugihartono (Asian Journal of Healthcare Analytics, 2026)
Radiation-induced esophageal stricture (RIES) represents a severe late complication in patients receiving radiotherapy, resulting in progressive dysphagia that can significantly impair quality of life. Several therapeutic options exist, including endoscopic dilation, injection therapy, incision, self-dilatation, surgical correction, and temporary stent placement. Among these, temporary esophageal stenting offers the potential advantage of providing sustained luminal expansion, stimulating tissue remodeling, and achieving long-term symptom relief. A 47-year-old woman with stage IV breast carcinoma and a prior history of radiotherapy presented with progressive difficulty swallowing. Over three months, her dysphagia worsened from solids to liquids. Endoscopic evaluation revealed a 4 cm esophageal stricture. Initial CRE balloon dilation improved her symptoms temporarily, but recurrence occurred, prompting a repeat endoscopy with adjunctive corticosteroid injection. Due to the relapse, a fully covered self-expandable metallic stent (SEMS) was placed to minimize the need for repeated dilations. The procedure was completed without complications. The management of benign esophageal strictures aims to reestablish luminal patency and alleviate dysphagia. SEMS placement represents an effective and reliable therapeutic option, particularly in cases of radiation-induced stricture where balloon dilation alone fails to achieve lasting results.